Internal Quality Control of Glucose During the Period of the on-Call Duty in a Biochemistry Laboratory in Antananarivo - Alain, Ntoe Zara; Koloina, Ranaivosoa Miora; Iorenantsoa , Razanadrakoto Ianja; Styvio, Velonjara; Olivat, Rakoto Alson Aimée; Andry, Rasamindrakotroka (International Journal For Research In Biology & Pharmacy, 2020)
Reliability is one of the priorities in medical analysis laboratories. Regular internal quality control allows us to validate and guarantee the good quality of the results of each test performed. The objective of this study was to evaluate the quality of the glucose analysis carried out in the biochemistry laboratory of the University Hospital Center of Joseph Ravoahangy Andrianavalona during the period of the on-call duty in a biochemistry laboratory in Antananarivo. It is a descriptive retrospective study carried out over a period of three months. The coefficient of variation was calculated using the quality control values of automaton BS 300 Mindray. Westgard rules were applied to analyze the Levey-Jennings graphs. To be precise the dosage must have a Coefficient of variation < 5,0 %. Coefficients of variation > 5.0 % were found in 50% of cases. To be accurate, a method must have a criterion 10% < 10. The assessment of the accuracy of the measuring tool showed that the amount of glycemia was generally within acceptable ranges. The Westgard rules were not always followed. Westgard's rule 10X was violated. Rule 13S was not followed in April and May. Rule 22S was violated in June. The training of interns in medical biology, the regular monitoring of internal quality controls and the search for the causes of errors could improve the quality of the results. This preliminary study provides information on the quality of our analytical process during the period of the on-call duty.